Sentralisasi Single Sign On (SSO) dengan Active Directory pada Windows Server - Ridlo, Ahmad Nur; , Bana Handaga, S.T.,M.T.,P.h.D (2016)
This research was conducted by figuring on the development aspect of technology especially in the information field. The big point on this research is the Single Sign On (SSO) system which commonly used in the web application. the web application processing in a large amount is often find a problem in the user authentication, it caused by too many accounts and passwords which every users should be memorized make the login process efficiency is not maximal. Here is the important role of the sso in controlling user to do the login process only once and it can automatically access all of the integrated web application. Central Authentication Service (CAS) or Lightweight Directory Access Protocol (LDAP) system is more dominant to be used as the development of sso in this present. Furthermore, in this research discusses the usage of the active directory in the windows operating system server as the center of sso. the utilization of active directory to make the optimum capability as sso supported by DNS service and Apache web service. DNS service is used as the domain and subdomain controller. Apache web service is used as the web page controller so it can be accessed by the user. The testing was conducted by making two domains which are domain and sub domain, both will be accessed by the user then. the access login by the user to one of the domains where the user's condition will change into active in whole web application either in domain or subdomain. Problems found in active directory utilization as sso is in webpage setting which need to have the user data in active status and accessible for another webpage either in domain or subdomain. To overcome those problems, cookies as the data stored in the web bowser application can be used, to make it accessible for all webpages either in the domain or subdomain with conditions using the same web browser application and device. The system assessment is limited by only using the local network procedure. The result from the system assessment is active directory has a login user capability up to twenty users in the same login time as according to the number of the available devices in the subject research point. The result of the service performance assesment of active directory in this research showed by the amount of the demand from the user in the same than can be handled without failure in range 10 up to 250 users. However, in the amount of 500 users demand found failures 0.4%.